Biology of the Copepod Ergasilus ogawai Kabata , 1992 Parasitic on Gills of Silurus triostegus at Garmat Ali River, North of Basrah City - Adday, T.K; Khamees, N. R; Balasem, A.N (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
During the period from September 1999 till August 2000, a tota l of 194 catfish Silurus triostegus were collected from Garmat Ali river, orth of Basrah city. Heavy infestation with Ergasilus ogawai was recorded on the gills of S. triostegus with an incidence of infection approaching 98.9% while the average intensity of infection was 417. The highest intensity recorded was 1985. The size of parasites and the shape of its cephalothorax and ovaries changed according to the age. The monthly observations on egg production indicated multibreeding with two main breeding seasons: spring and autumn. Preliminary laboratory study revealed the yield of nauplius I and nauplius II larval stages from hatching of eggs in petri dishes. This copepod pierces its claws in the gill filaments of the host. It feeds on blood, gill tissues and body fluids.